2018
DOI: 10.1051/e3sconf/20183401001
|View full text |Cite
|
Sign up to set email alerts
|

The mechanical properties of brick containing recycled concrete aggregate and polyethylene terephthalate waste as sand replacement

Abstract: Abstract. This research focuses on the performance of composite sand cement brick containing recycle concrete aggregate and waste polyethylene terephthalate. This study aims to determine the mechanical properties such as compressive strength and water absorption of composite brick containing recycled concrete aggregate (RCA) and polyethylene terephthalate (PET) waste. The bricks specimens were prepared by using 100% natural sand, they were then replaced by RCA at 25%, 50% and 75% with proportions of PET consis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 11 publications
3
3
0
Order By: Relevance
“…The increasing number of PET waste substitutions affects the compressive strength. This study corresponds to previous studies, where PET waste addition leads to a reduction of the sample's compressive strength [41], [42], [46] and [61].…”
Section: Compressive Strength Testsupporting
confidence: 89%
See 2 more Smart Citations
“…The increasing number of PET waste substitutions affects the compressive strength. This study corresponds to previous studies, where PET waste addition leads to a reduction of the sample's compressive strength [41], [42], [46] and [61].…”
Section: Compressive Strength Testsupporting
confidence: 89%
“…PET was known as a material with a low density and lower value of specific gravity, which proved the replacement of sand with these materials contributed to the reduction in mass of the brick samples [42]. This study had the same pattern as the studies conducted by Davies and Olofinnade [57], Bijivemula and Noolu [46], and Khalid et al, [41], which revealed that the density decreases with the increase in the PET waste content in the sample composition.…”
Section: Densitysupporting
confidence: 66%
See 1 more Smart Citation
“…Currently, the incorporation of plastic waste into building materials is being investigated by many researchers. For example, plastic waste is replaced as fine aggregate [5], and Pet fibres are incorporated into concrete to improve compressive strength and Pet bottles are filled with soil [6][7]. Incorporating plastic waste in building materials has positively effects on various material properties such as compressive strength, density and water absorption.…”
Section: Introductionmentioning
confidence: 99%
“…According to Senthamarai et al [11], concrete which contain at least 20% a waste product whether it from the agriculture, daily waste or C&D waste is called green concrete that will create a sustainable development. The simple definition of sustainable development is the possibility to achieve the needs of present generation without preventing the future generation to meet their needs [12], [13]. To accomplish that needs, this review paper was conducted to gather an overview information on FRCA properties such as density and water absorption and the performance of concrete incorporating with FRCA in terms of compressive strength and splitting tensile strength regarding the percentage of FRCA replacement.…”
Section: Introductionmentioning
confidence: 99%